Rancang Bangun Alat Pendeteksi Kebocoran dan Tingkat Kandungan Gas dalam Ruangan Berbasis Mikrokontroler - Agusta, Ikraam; Rama, Yayan; Pratama, Yogi (YASIN, 2023)
The purpose of this research is to describe the design of a microcontroller-based leak detection device and the level of gas content in a room. The data collection method was carried out by means of literature study methods and laboratory research. In this study, several graphical methods were used to visualize and understand the data flow and transformations in the system. System design in this study is in the form of Context Diagrams, Data Flow Diagrams, Block Diagrams, Flowcharts. As for the results of the design of the leak detection device and the gas content in the room, it can be concluded 4 things as follows. First, the Arduino microcontroller, either Arduino Uno or Arduino Mega, is able to properly control the leak detector and gas content in the room. Second, the LCD can display information on the gas content in the room. Third, the Gas Sensor can properly detect gas and activate the LED and buzzer as an alarm. Fourth, the final results of the overall test for the leak detector and the gas content in the room are as expected.